MARCION OF SYNOPE’S RELEVANCE IN THE CONTEMPORARY WORLD VIS-À-VIS RELIGIOUS VIOLENCE - G Andrade (Acta Theologica)
Marcion of Synope has long been considered a heretic by all Christian churches. He is frequently grouped with the Gnostic trends of Early Christianity, although this is not entirely accurate. While he made a handsome financial contribution to the Church of Rome, he was eventually excommunicated. Yet, even if his doctrines can seem extravagant, contradictory, alien to modern values, and even anti-Semitic, his theology is relevant in our contemporary world because of the ever-growing threat of religious violence and fundamentalism. In his attempt to cleanse Christianity of its Jewish elements, Marcion set the bases for a critique of the cult to a violent God and the divine inspirations of violence. Marcion believed that the Old Testament God (Yahweh) was, in fact, the same as the creator or the material world, from which we must escape. He contrasted that God’s violent deeds with the peaceful nature and character of the New Testament God.